In vitro comparative study of penetration and degree of microfiltration of two pits and fissures sealants (ionomeric and composite resins): influence on the application technique - Avilés Erazo, Jéssica (2020)
Objetives: to compare the penetration capacity and the degree of microfiltration between a resinous sealant and an ionomer with and without ameloplasty, and with or without the placement of an adhesive prior to the placement of the resinous sealant. Methodology: 90 donated premolars, free of caries obtained previous indication orthodontic, later prophylaxis, were divided into six groups, in G1: ameloplasty was performed, acid etching, resinous sealant application, G2: ameloplasty, acid etching, adhesive application and sealant resinous, G3: acid etching, application of adhesive and resinous sealant, G4: application of ionomeric sealant, G5: acid etching, application of resinous sealant, G6: ameloplasty, application of ionomeric sealant. After thermocycling, the teeth were sectioned and the fragments observed under stereomicroscope and observation to the Scanning Electron Microscope. Results: he lowest degree of microfiltration was detected in the group undergoing ameloplasty, acid etching, application of adhesive and resinous sealant (0.198 mm). There was greater penetration of the sealant with the ameloplasty technique. Conclusions: The placement of adhesive prior to the resinous sealant influenced the degree of microfiltration, and the performance of ameloplasty helps with greater penetration of the sealant material.